Improving High School Adolescents Optimism Through a Best Possible Self Intervention - Rahman Pranovri Putra; Alnico Imam Nugroho; Anindhita Sasanti Rahajeng; Andi Fenita Aysila (Journal of Psychology and Instruction, 2024)
Adolescents will inevitably face challenges and obstacles in their educational journey, so an optimistic mindset is essential for positive problem-solving. The "Best Possible Self" technique stands out as an effective strategy to foster optimism. This study aims to evaluate the effectiveness of applying the "Best Possible Self" method in increasing students' level of optimism. Using a True Experimental design with a control group, this study involved a pretest and posttest of 16 grade XI students at SMA Islam 3 Pakem, who were randomly selected. Data analysis used paired sample test and independent t-test. The results showed the success of the Best Possible Self intervention, which showed a substantial mean difference from the experimental group and for the control group there was no difference. In addition, significant differences between the experimental and control groups. The findings provide benefits for students and educators in adopting the Best Possible Self method as a tool to increase optimism and expand understanding in positive psychology.